The effect of body condition score in the transition period on milk, fertility, and health traits of Holstein cows - Ariadna V. Alvarado; Alan S. Alvarado; Fernando Arellano; Francisco G. Véliz; Ángeles de Santiago; Viridiana Contreras; Miguel Mellado (Mljekarstvo)
This study aimed to investigate the relationship between measures of body condition score (BCS) during the transition period and milk yield, reproductive performance, and occurrence of metritis and ketosis in cows. A total of 5026 lactations of 2424 Holstein cows from a single dairy farm were assessed for BCS (5-point scale; 0.25-point increments) 15 days precalving, at calving, and first service. ΔBCS were classed as <0.25, 0.25-0.5, 0.5-0.75, and >0.75 from 15 days precalving to parturition and from calving to first artificial insemination. BCS classes at parturition were <3.5, 3.5-3.75, and >3.75. 305-d milk yield was the highest in cows with BCS change (ΔBCS) <0.25 between 15-d precalving and parturition (11526±1088 kg), and the lowest (10878±1114) in cows with precalving ΔBCS <0.75. The total milk yield was the highest in cows with ΔBCS <0.25 between 15-d precalving and parturition (13861±2541 kg), and lowest (13214±3174) in cows with precalving ΔBCS >0.75. The overall pregnancy rate was least [281/836 (33.6%); p<0.01] for cows that lost >0.75 units of BCS, and greatest for cows that lost <0.25 BCS [477/615 (77.6 %)]. Puerperal metritis occurred more often in cows that lost >0.75 BCS between calving and the first artificial insemination (AI) [175/836 (20.9 %); p<0.01). Cows with reduced BCS loss between calving and first AI were less likely to present metritis [67/615 (10.9 %); p<0.01], whereas cows with ≥ 0.75 BCS loss between calving and first AI were 2.3 times more likely [175/836 (20.9 %)] to suffer metritis. In conclusion, greater changes in BCS between calving and first AI increased 305-d and the total milk yield, and occurrence of puerperal metritis and clinical ketosis, although fertility was reduced.